Nickel, le trésor des Kanak directed by Laurent Cibien and Anne Pitoiset. - Pitoiset, Anne.; Cibien, Laurent. (Ethnographic video online, 2013)
For 25 years, Kanak have fought to obtain their share of the wealth rising from mining in New Caledonia. This film relates their struggle.